मुक्त फाउन्डेशन, पोखराद्वारा आयोजित प्रथम ऋग्वैदिक हिमालय अन्तर्राष्ट्रिय सम्मेलनमा प्रस्तुत वक्तव्य {Presentation at the 1st Rigvedic Himal International Conference organized by Mukta Foundation, Pokhara} (Rigvedic Himalaya, 2024)
Not Available.